Nanoscale patterning of self-assembled monolayer (SAM)-functionalised substrates with single molecule contact printing. Issue 39 (2nd October 2017) - Sajfutdinow, M.; Uhlig, K.; Prager, A.; Schneider, C.; Abel, B.; Smith, D. M.
Abstract : DNA origami stamps print biomolecules onto SAM-coated gold films via bioconjugation in a process called single molecule contact printing. Abstract : Defined arrangements of individual molecules are covalenty connected ("printed") onto SAM-functionalised gold substrates with nanometer resolution. Substrates were initially pre-functionlised by coating with 3, 3′-dithiodipropionic acid (DTPA) to form a self-assembled monolayer (SAM), which was characterised by atomic force microscopy (AFM), contact angle goniometry, cyclic voltammetry and surface plasmon resonance (SPR) spectroscopy. Pre-defined "ink" patterns displayed on DNA origami-based single-use carriers ("stamp") were covalently conjugated to the SAM using 1-ethyl-3-(3-dimethylamino-propyl)carbodiimide (EDC) and N -hydroxy-succinimide (NHS). These anchor points were used to create nanometer-precise single-molecule arrays, here with complementary DNA and streptavidin. Sequential steps of the printing process were evaluated by AFM and SPR spectroscopy. It was shown that 30% of the detected arrangements closely match the expected length distribution of designed patterns, whereas another 40% exhibit error within the range of only 1 streptavidin molecule. SPR results indicate that imposing a defined separation between molecular anchor points within the pattern through this printing process enhances the efficiency for association of specific binding partners for systems with high sterical hindrance. This study expands upon earlier findings where geometrical information was conserved by the application of DNA nanostructures, by establishing a generalisable strategy which is universally applicable to nearly any type of prefunctionalised substrate such as metals, plastics, silicates, ITO or 2D materials.